Neutralization of crotaline snake venoms from Central and South America by antivenoms produced in Brazil and Costa Rica - Bogarín, Guisella (2000)
A study was performed on the ability of antivenoms, produced in Brazil and Costa Rica, to neutralize lethal, hemorrhagic and coagulant activities of the venoms of 16 species of Central and South American snakes of the subfamily Crotalinae. Neutralization of lethality was studied by two different methods routinely used in the quality control of antivenoms at Instituto Butantan (IB) and Instituto Clodomiro Picado (ICP). Both antivenoms neutralized the majority of the venoms studied, but the values of effective doses 50% (ED50) differed markedly depending on the method used. In general, higher potencies were obtained with the method of ICP, where a challenge dose corresponding to 4 LD50s is used, than with the method of IB, where a challenge dose of 5 LD50s is employed. All venoms induced hemorrhagic activity in the mouse skin test, which was effectively neutralized by the two antivenoms. All venoms, except those of Porthidium nasutum and Bothriechis lateralis, induced coagulation of human plasma in vitro and both antivenoms were effective in the neutralization of this activity. In conclusion, our results provide evidence of an extensive cross reactivity between these antivenoms and Central and South American crotaline snake venoms.